Neuroanatomical Abnormalities in Adolescent ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Twenty-four adolescents with familial ADHD and 10 control youths underwent high-resolution structural MRI, and frontal lobe gyri and caudate were compared in a study at Stanford University and other US centers.